Analysis of Energy Efficiency Level of Typical Countries. Issue 1 (March 2021) - Wang, Junhai; Yin, Jianbing; Chen, Lin; Chen, Zhiyuan; Gong, Yingfei; Tan, Qingkun
Abstract: The current global energy transition is in a period of acceleration, and the transition process of various countries shows certain characteristics of differentiation. Based on the analysis of the development direction of the energy transition, this paper proposes covering energy structure and energy efficiency. On this basis, a comparative analysis of the energy transition situations of major countries such as China, the European Union, Germany, and Japan was carried out, and then conclusions and enlightenments for my country's energy transition were put forward.